Influence of gender and oral contraceptives on CYP2D6 and CYP2C19 activity in healthy volunteers - Hägg, Staffan (Blackwell Science Inc, 2001)
AIMS: The study was carried out in order to assess the effects of gender and the use of oral contraceptives (OCs) on CYP2D6 and CYP2C19 activities in healthy volunteers. METHODS: Six hundred and eleven Caucasian volunteers (330 males and 281 females; age range 18–49 years) were phenotyped with respect to CYP2D6 and CYP2C19 by means of the probe drugs dextromethorphan and mephenytoin, respectively. Extensive metabolisers were selected for this study. RESULTS: The median dextromethorphan/dextrorphan metabolic ratio in non-OC using females was significantly lower than in males (0.067 vs 0.080; P = 0.033) (mean difference in ln dextromethorphan/dextrorphan metabolic ratio 0.023, 95% CI 0.03–0.43). For the mephenytoin S/R ratio, no such difference was observed. However, OC using females had a significantly higher median mephenytoin S/R ratio than non-OC using females (0.230 vs 0.090; P < 0.001) (mean difference in ln mephenytoin S/R ratio 0.082, 95% CI 0.60–1.04). Moreover, females using combined OCs had a significantly higher median ratio than females using OCs with progestins only (median 0.258 vs 0.135; P = 0.008) (mean difference in ln mephenytoin S/R ratio 0.82, 95% CI 0.21–1.34). CONCLUSIONS: Given certain assumptions, the study indicates that females in the fertile age have a slightly higher CYP2D6 activity compared with males. There was no evidence of a gender difference in CYP2C19 activity. The use of combined OCs reduces the activity of CYP2C19, an effect that seems to be related to the ethinyloestradiol component.